Root causes and preventability of emergency department presentations of older patients: a prospective observational study - Cordula Wagner; Prabath W B Nanayakkara; Hanneke Merten; Babiche Driesen; Rosalie Barendregt; H Jaap Bonjer (BMJ Open, 2021)
Objective More older patients are presenting to the emergency department (ED). It is important to know why these patients present and if the ED is the best place for them to receive the care they need. The primary aim of this study was to identify organisational-related, technical-related, healthcare worker-related and patient-related factors leading to ED presentations of older patients. The secondary aim was to determine patients’ and caregivers’ perspectives on what kinds of ED presentations are potentially preventable.Design This is a prospective observational study. A root cause analysis was performed by the Prevention and Recovery Information System for Monitoring and Analysis method. It used basic administrative data collected from patient records and interviews of patients, general practitioners (GPs) and physicians at the ED.Setting The ED of an academic hospital in the Netherlands.Participants 100 older patients (aged ≥70 years) who attended the ED between November 2017 and March 2018.Results In 100 patients presenting to the ED, 159 factors that contributed to presentation were identified; most of these factors were related to underlying diseases (59%) and patient-related factors (18%). These presentations were considered potentially preventable by 23% of the physicians at the ED and 21% of the GPs, but only 10% of the patients. In only four cases was there overall agreement between the patients and the healthcare workers.Conclusion The most frequent underlying factors contributing to an ED presentation in older patients are disease-related and patient-related. The low percentage of ED presentations considered potentially preventable shows that a ‘preventable ED presentation’ is difficult to define and therefore interventions to reduce them are unlikely to be simple. Novel solutions within the acute care pathway are required in order to deliver care of optimal quality and safety to older patients.